2014
DOI: 10.1111/desc.12209
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the developing brain to emotional body expressions

Abstract: Reading others' emotional body expressions is an essential social skill. Adults readily recognize emotions from body movements. However, it is unclear when in development infants become sensitive to bodily expressed emotions. We examined event‐related brain potentials (ERPs) in 4‐ and 8‐month‐old infants in response to point‐light displays (PLDs) of happy and fearful body expressions presented in two orientations (upright and inverted). The ERP results revealed that 8‐month‐olds but not 4‐month‐olds respond se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 52 publications
13
55
1
Order By: Relevance
“…That is, adults’ emotion recognition rates from inverted body expressions are still above chance. Similarly, in prior ERP work with infants (Missana et al, 2014a) using dynamic body expressions, while there was a significant main effect of emotion (fearful, happy), no evidence for an interaction between the emotion and orientation (upright, inverted) was obtained, which is probably to do with the fact that ERP modulations occurred in a similar direction for upright and inverted displays of emotion. However, further analysis revealed that only in the upright condition did infants’ neural responses discriminate between emotions (Missana et al, 2014a).…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…That is, adults’ emotion recognition rates from inverted body expressions are still above chance. Similarly, in prior ERP work with infants (Missana et al, 2014a) using dynamic body expressions, while there was a significant main effect of emotion (fearful, happy), no evidence for an interaction between the emotion and orientation (upright, inverted) was obtained, which is probably to do with the fact that ERP modulations occurred in a similar direction for upright and inverted displays of emotion. However, further analysis revealed that only in the upright condition did infants’ neural responses discriminate between emotions (Missana et al, 2014a).…”
Section: Introductionmentioning
confidence: 54%
“…Similarly, in prior ERP work with infants (Missana et al, 2014a) using dynamic body expressions, while there was a significant main effect of emotion (fearful, happy), no evidence for an interaction between the emotion and orientation (upright, inverted) was obtained, which is probably to do with the fact that ERP modulations occurred in a similar direction for upright and inverted displays of emotion. However, further analysis revealed that only in the upright condition did infants’ neural responses discriminate between emotions (Missana et al, 2014a). We hypothesized that neural evidence for emotion discrimination is related to the orientation of the body; however, given previous findings, we expected that this effect might not be directly reflected in a significant interaction between stimulus orientation and emotion.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations